Ibn Sa‘d’s Kitab Al-Tabaqat Al-Kabir and the Narratives of the Signs of Muhammad’s Prophethood: A Historiographical Study - Fuad, Ahmad Nur (Universitas Islam Negeri Sumatera Utara, 2025)
This article conducts an in-depth analysis of the signs of Muhammad's prophethood as presented in Ibn Sa‘d’s Kitab al-Tabaqat, using a historiographical approach to explore these narratives’ significance in early Islamic history. It seeks to identify and categorize the range of signs and miracles attributed to the Prophet Muhammad, investigate Ibn Sa‘d’s interpretive techniques and historical methods, and examine how these signs help construct prophetic authority and Islamic cultural memory. By analyzing each narrative in both its historical context and its theological and literary dimensions, the study addresses key issues such as Ibn Sa‘d’s perspective as a historian, his interpretive biases, and the ways these narratives reinforce Islamic belief in Muhammad’s divine mission. The findings reveal that Ibn Sa‘d’s portrayal of prophetic signs operates on several levels: as a testament to divine intervention, an assertion of the Prophet's unique spiritual status, and a framework for defining the sacred in Islamic tradition. This article argues that Ibn Sa‘d’s narratives provide critical insights into Islamic historical methodology and the formation of religious identity, enhancing our understanding of the intersections of history, theology, and memory in shaping early Islamic religio-cultural consciousness.